(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the colonization processes of South Ukraine in the XVIII century. The author tries to regard this problem and compare the features of colonization of the Steppe Ukraine with the colonization of settlements of New Serbia (1751ñ1764), also the Novoslobidskiy cossack regiment (1753ñ1764) is ressearched. The reasons of the organization establishment are considered, and also contribution of these settlements to the settling and mastering of south of Ukraine is analysed.